A light green fireproof decorative panel and preparation method thereof

By using modified reed straw fibers and high-performance fillers, combined with polypropylene resin and polyvinyl chloride resin, a lightweight green fire-resistant veneer is prepared, which solves the flexibility and compressive tensile properties of traditional straw-based wood veneer panels. The problem of insufficient results enables high-performance decorative panel products.

CN119058203BActive Publication Date: 2025-02-18INNER MONGOLIA MENGMA BOARD IND CO LTD

Patent Information

Application Number
CN202411556416.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-18
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The existing straw-based wood plastic veneer panels lack flexibility and compressive tensile resistance, which leads to certain shortcomings in their applications. Especially in cases such as roof ceilings, traditional bamboo and wood fiber substrates have a large weight and are not suitable for application.

Method used

Reed straw fibers are used as the base material, and the waxy layer on the surface of reed straw is destroyed by thermal grinding, and connected to caffeic acid to form active groups with more hydroxyl and carboxylic groups, and then with bean-based adhesive and MDI adhesive. Reaction to form a fine mesh structure. At the same time, polypropylene resin and polyvinyl chloride resin are used as plastic materials, and mixed fillers of shell powder and diatomaceous earth modified by the surface of the aluminum-titanium composite coupling agent JTW-1816 are filled to enhance their hardness, static bending strength, elastic modulus and Heat resistance.

Benefits of technology

The lightweight green fireproof decorative panel prepared has excellent waterproof and moisture resistance, high wear resistance, large glue strength, good impregnation and peeling performance, cold and heat resistance, pollution resistance and flame retardant performance, and the formaldehyde emission is almost zero, which is safe and environmentally friendly. .

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of decorative panels, and specifically discloses a light green fireproof decorative panel and a preparation method thereof. A light green fireproof decorative panel, using polypropylene resin, polyvinyl chloride resin, caffeic acid modified reed straw fiber, shell powder and diatomaceous earth mixed filler modified with aluminum titanium composite coupling agent JTW‑1816 as main raw materials, using bean-based adhesive and MDI adhesive as binders to prepare a light green base material, using ultra-thin fiberboard as a decorative material, and using vinyl chloride copolymer emulsion, bean-based adhesive and MDI adhesive as finishing film materials, to jointly prepare a light green fireproof decorative panel with excellent performance. The light green fireproof decorative panel prepared in the present application has the advantages of being waterproof and moisture-proof, high wear resistance, high bonding strength, good impregnation and peeling performance, resistance to cold and heat cycles, pollution resistance, excellent flame retardant performance, safety and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of decorative panels, and more specifically, to a lightweight green fireproof decorative panel and a preparation method thereof. Background Art

[0002] Wood veneer, full name decorative veneer plywood, is a surface material used for interior decoration or furniture manufacturing, which is made by slicing natural wood or technical wood into thin slices of a certain thickness, adhering them to the surface of plywood, and then hot pressing. In simple terms, veneer consists of veneer layers and base layers.

[0003] There are generally two types of common decorative panels on the market. One is stone-plastic based decorative panels, which are produced with stone powder as aggregate. Stone-plastic decorative panels are generally hard, rigid, poor in toughness, high in density and high in transportation cost. The other is wood-plastic based decorative panels. The wood-plastic substrate is mainly made of wood as the basic material with thermoplastic polymer materials and processing aids, which are mixed evenly and then extruded into shape through mold equipment. It has strong processability and is waterproof, moisture-proof and insect-proof.

[0004] The main materials of wood plastic substrates include bamboo or straw. Compared with bamboo fiber substrates, straw substrates are more resistant to carbonization and insect infestation. At the same time, due to the heavy weight of bamboo fiber substrates, they are not suitable for roof ceilings. Straw as a substrate has the characteristics of lightness.

[0005] The total amount of straw produced in my country each year is huge, but the utilization rate is very low. In rural areas of my country, straw is basically treated by burning or crushing and returning to the field. Burning not only wastes natural resources, but also increases the concentration of inhalable particulate matter of sulfur dioxide and nitrogen dioxide in the air, causing harm to people's lives and health; returning straw to the field, without fermentation in the short term, has no promoting effect on the improvement of soil quality. Another role of straw is shown in the construction field: straw was mainly used for thatched houses and reed straw roofs in the early days, and later used as wall materials such as bricks and boards. Using straw as the base material of decorative panels has the characteristics of lightness and environmental protection. Straw-based decorative panels combine many advantages of plant fibers and plastic polymer materials, can replace wood in large quantities, and can effectively alleviate the contradiction between the scarcity of forest resources and the shortage of wood supply in my country. It is a low-carbon, green, recyclable and renewable ecological plastic wood material with great development prospects.

[0006] At present, due to the good flexibility of bamboo and wood, as well as strong compressive and tensile properties, and the relatively poor flexibility of straw fiber, there is more development of wood-plastic-based decorative panels made of bamboo and wood as raw materials, while there is less research on straw-based wood-plastic-based decorative panels. Summary of the invention

[0007] In order to further improve the comprehensive quality of straw-based wood-plastic decorative panels, the present application provides a lightweight green fireproof decorative panel and a preparation method thereof.

[0008] In the first aspect, the present application provides a lightweight green fireproof decorative panel, which adopts the following technical solution:

[0009] A light green fireproof decorative panel comprises a substrate, both sides of which are bonded with ultra-thin fiberboards, and the outer side of the ultra-thin fiberboard is bonded with a decorative film material; the substrate comprises reed straw fiber, polypropylene resin, polyvinyl chloride resin, modified filler, MDI adhesive, and soy-based adhesive; the mass ratio of the reed straw fiber, polypropylene resin, polyvinyl chloride resin, modified filler, MDI adhesive, and soy-based adhesive is (50-70): (20-30): (35-55): (30-50): (5-10): (3-8).

[0010] By adopting the above technical scheme, a lightweight and green substrate was prepared with polypropylene resin, polyvinyl chloride resin, reed straw fiber modified by caffeic acid, shell powder and diatomaceous earth mixed filler modified by aluminum-titanium composite coupling agent JTW-1816 as main raw materials, soy-based adhesive and MDI adhesive as binders, ultra-thin fiberboard as decorative material, vinyl chloride copolymer emulsion, soy-based adhesive and MDI adhesive as decorative film materials, and jointly prepared a lightweight green fireproof decorative panel which is waterproof and moisture-proof, has high wear resistance, high bonding strength, good impregnation and peeling performance, is resistant to cold and heat, is resistant to pollution, has excellent flame retardant performance, has almost zero formaldehyde emission, and is safe and environmentally friendly.

[0011] Preferably, the ultra-thin fiberboard has a thickness of 0.25-0.45 mm and a density of 0.9-1.1 g / m 3 .

[0012] By adopting the above technical solution, the ultra-thin fiberboard under this condition is selected to be bonded to help improve the comprehensive performance of the lightweight green fireproof decorative panel.

[0013] Preferably, the finishing film material includes vinyl chloride copolymer emulsion, silica sol, and methacryloxymethyltrimethoxysilane.

[0014] The substrate is prepared by the following steps: (1) steaming reed straw at 150-170°C for 8-10 minutes, and then placing it in a hot mill at 180-200°C for 10-20 minutes to obtain reed straw hot fibers; adding caffeic acid and 1-1.2 g / mL ascorbic acid solution to the reed straw hot fibers, and then adding 0.5-0.8 g / mL hydrogen peroxide solution, stirring at 70-90°C for 10-30 minutes, and then filtering and drying to obtain reed straw fibers, wherein the amount ratio of the reed straw fibers, caffeic acid, ascorbic acid and hydrogen peroxide solution is (50-100) g: (10-18) g: (2-3) mL: ( 10-20) mL; (2) weigh shell powder and diatomaceous earth in a mass ratio of (1.5-2):1, and dry at 100°C until the water content is less than 0.3-0.5% to obtain a mixed filler; add the dried mixed filler into anhydrous ethanol and ultrasonically disperse it for 30-50 minutes, then add aluminum-titanium composite coupling agent JTW-1816 and react at 90-100°C for 15-20 minutes, filter and obtain a modified filler, wherein the amount of aluminum-titanium composite coupling agent JTW-1816 added is 2-2.8% of the mass of the mixed filler; (3) mix reed straw fiber, polypropylene resin, polyvinyl chloride resin, modified filler, soybean-based adhesive and MDI adhesive, and extrude and mold to obtain a substrate.

[0015] The thickness of the substrate is 2-3 mm.

[0016] By adopting the above technical scheme, reed straw is used as the fiber raw material instead of traditional wood fiber as the base material of the decorative panel. Compared with other straws, reed straw fiber has a higher aspect ratio and can achieve good plasticity and structural strength, but the active hydroxyl groups on the surface of reed straw are relatively few; in addition, the wax layer on the surface of reed straw is destroyed by thermal grinding treatment, and active groups with more hydroxyl groups and carboxyl groups are formed on the surface of reed straw by connecting with caffeic acid, and then reacting with bean-based adhesive and MDI adhesive to form a fine network structure. At the same time, polypropylene resin and polyvinyl chloride resin are used as plastic materials to enhance their weather resistance, aging resistance and waterproof properties, and filled with shell powder and diatomaceous earth mixed fillers modified with aluminum-titanium composite coupling agent JTW-1816. Through the modification of aluminum-titanium composite coupling agent JTW-1816, the compatibility of shell powder and diatomaceous earth with resin is enhanced, so that they are evenly dispersed, thereby increasing their hardness, static bending strength, elastic modulus and heat resistance.

[0017] Preferably, the preparation method of the decorative film material is as follows: (1) mixing sodium di(2-ethylhexyl) succinate sulfonate, water, and silica sol with a concentration of 20-30wt%, adding dodecanol, ultrasonically dispersing, adjusting the pH of the system to 4.5-5.5, then adding methacryloxymethyltrimethoxysilane, ultrasonically dispersing for 20-30min, and then stirring at 240-260°C to obtain a silica sol solution, wherein the sodium di(2-ethylhexyl) succinate sulfonate, water, silica sol, dodecanol, and silica sol are mixed. The dosage ratio of glycol and methacryloyloxymethyl trimethoxysilane is (2.5-5.5) g: (20-30) mL: (10-15) mL: (0.5-0.8) g: (5-8) mL; (2) sodium di(2-ethylhexyl) succinate sulfonate, ammonia water, nonylphenol polyoxyethylene ether and water are mixed to obtain a mixed solution, the silica sol solution is adjusted to neutral and added to the mixed solution, and then tert-butyl acrylate, hexafluorobutyl acrylate, vinyl chloride and dodecanol are added to obtain a pre-emulsified solution. (3) heating the pre-emulsified liquid to 75-80°C in a water bath under a nitrogen atmosphere and keeping the temperature for 25-35 minutes, then adding ammonium persulfate and reacting for 3-5 hours to obtain a vinyl chloride copolymer emulsion; the amount ratio of the sodium di(2-ethylhexyl) succinate sulfonate, ammonia water, nonylphenol polyoxyethylene ether, water, silica sol liquid, tert-butyl acrylate, hexafluorobutyl acrylate, vinyl chloride, dodecanol, and ammonium persulfate is (2.5-5.5) g: (5-10) mL: (0.8-1. 2) g: (10-20) mL: (40-50) mL: (8-10) g: (5.5-7.5) g: (13-18) g: (0.5-0.8) g: (0.7-1.2) g; (4) Add soybean-based adhesive and MDI adhesive into vinyl chloride copolymer emulsion, mix evenly, and obtain a decorative film material; the dosage ratio of soybean-based adhesive, MDI adhesive, and vinyl chloride copolymer emulsion is (2-3) g: (2.5-4) g: (40-60) g.

[0018] By adopting the above technical scheme, the silica sol is modified by methacryloyloxymethyltrimethoxysilane, and then the silica and resin are chemically connected by emulsion copolymerization. The silica is filled by emulsion copolymerization to increase the wear resistance and hardness of the decorative film. The hydrophobic and anti-pollution properties are increased by adding tert-butyl acrylate and hexafluorobutyl acrylate.

[0019] Preferably, the green fireproof decorative panel further comprises an edge banding strip, and the material of the edge banding strip is any one of EVA, ABS, PVC and PUR.

[0020] In the second aspect, the present application provides a method for preparing a lightweight green fire-retardant decorative panel, comprising the following steps: S1, uniformly coating the decorative film material on the surface of an ultra-thin fiberboard, and hot pressing for 10-12 minutes at 140-150°C and 1.2-1.6MPa to form a decorative film with a thickness of 0.30-0.50mm; S2, then bonding the decorative film to the surface of the substrate, and then using a hot press to perform hot pressing and curing, the hot pressing conditions are: 160-180°C, 1.5-1.8MPa, time 15-20min, to obtain a lightweight green fire-retardant decorative panel.

[0021] Also includes: S3, grinding the edges of the lightweight green fireproof veneer panels to be smooth, and then using edge banding strips to seal the edges of the lightweight green fireproof veneer panels.

[0022] In summary, this application has the following beneficial effects:

[0023] 1. This application uses polypropylene resin, polyvinyl chloride resin, caffeic acid-modified reed straw fiber, shell powder modified with aluminum-titanium composite coupling agent JTW-1816 and diatomaceous earth mixed filler as main raw materials, soybean-based adhesive and MDI adhesive as binders to prepare a lightweight green substrate, ultra-thin fiberboard as the facing material, and vinyl chloride copolymer emulsion, soybean-based adhesive and MDI adhesive as the facing film material to jointly prepare a lightweight green fire-retardant decorative panel with excellent performance.

[0024] 2. In the present application, reed straw is preferably used as the fiber raw material instead of traditional wood fiber. Reed straw fiber has a high aspect ratio. As the base material of the decorative panel, it can achieve good plasticity and structural strength. However, the surface active hydroxyl groups of reed straw are relatively few. In the present application, the wax layer on the surface of reed straw is destroyed by heat grinding treatment, and active groups with more hydroxyl groups and carboxyl groups are formed on the surface of reed straw by connecting with caffeic acid, and then reacting with bean-based adhesive and MDI adhesive to form a fine network structure. At the same time, polypropylene resin and polyvinyl chloride resin are used as plastic materials to enhance their weather resistance, aging resistance and waterproof properties, and filled with shell powder and diatomaceous earth mixed filler modified with aluminum-titanium composite coupling agent JTW-1816. The shell powder and diatomaceous earth are modified by aluminum-titanium composite coupling agent JTW-1816 to enhance the compatibility of the resin and make them evenly dispersed, thereby increasing their hardness, static bending strength, elastic modulus and heat resistance.

[0025] 3. In the present application, methacryloyloxymethyltrimethoxysilane is preferentially used to modify the silica sol, and then the silica and resin are chemically connected by emulsion copolymerization to obtain a finishing film material. The silica is filled by emulsion copolymerization to increase the wear resistance and hardness of the finishing film material, and the hydrophobic and anti-pollution properties are increased by adding tert-butyl acrylate and hexafluorobutyl acrylate.

[0026] 4. The lightweight green fireproof decorative panel prepared by the preparation method of the present application is waterproof and moisture-proof, has high wear resistance, high bonding strength, good immersion and peeling performance, is cold-resistant and heat-resistant, pollution-resistant, has excellent flame retardant properties, has almost zero formaldehyde emission, and is safe and environmentally friendly. DETAILED DESCRIPTION

[0027] The present application is further described in detail below with reference to the embodiments.

[0028] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0029] Example 1

[0030] A light green fireproof decorative panel comprises a substrate, both sides of the substrate are laminated with ultra-thin fiberboards, and the outer side of the ultra-thin fiberboard is laminated with a decorative film material;

[0031] The substrate is prepared by the following steps:

[0032] (1) The reed straw was steamed at 150°C for 10 min, and then placed in a hot mill at 180°C for 20 min to obtain reed straw hot fiber; 10 g of caffeic acid and 2 mL of 1.2 g / mL ascorbic acid solution were added to 50 g of reed straw hot fiber, and then 10 mL of 0.8 g / mL hydrogen peroxide solution was added, stirred at 70°C for 30 min, and then filtered and dried at 70°C for 24 h to obtain reed straw fiber;

[0033] (2) Weigh shell powder and diatomaceous earth in a mass ratio of 1.5:1, and dry at 100°C until the water content is less than 0.3% to obtain a mixed filler; add the dried mixed filler into anhydrous ethanol and ultrasonically disperse for 30 minutes, then add aluminum-titanium composite coupling agent JTW-1816 and react at 90°C for 20 minutes, filter and obtain a modified filler, wherein the amount of aluminum-titanium composite coupling agent JTW-1816 added is 2% of the mass of the modified filler;

[0034] (3) Reed straw fiber, polypropylene resin, polyvinyl chloride resin, modified filler, MDI adhesive and soybean-based adhesive were mixed evenly in a mass ratio of 50:20:35:30:5:3, and extruded to obtain a substrate with a thickness of 2 mm.

[0035] The ultra-thin fiberboard has a thickness of 0.25 mm and a density of 0.9 g / m 3 .

[0036] The preparation method of the decorative film material is as follows: (1) sodium di(2-ethylhexyl) succinate sulfonate, water, and silica sol with a concentration of 20wt%, add dodecanol, ultrasonically disperse, adjust the system pH to 4.5, then add methacryloxymethyltrimethoxysilane, ultrasonicate for 20 minutes, and then stir at 240°C to obtain a silica sol solution, wherein the amount ratio of sodium di(2-ethylhexyl) succinate sulfonate, water, silica sol, dodecanol, and methacryloxymethyltrimethoxysilane is 2.5g:20mL:10mL:0.5g:5mL; (2) sodium di(2-ethylhexyl) succinate sulfonate, ammonia water, nonylphenol polyoxyethylene ether and water are mixed to obtain a mixed solution, adjust the silica sol solution to neutral and add the mixed solution, then add tert-butyl acrylate and acrylic acid Hexafluorobutyl ester, vinyl chloride and dodecanol to obtain a pre-emulsion; (3) heating the pre-emulsion to 75°C in a water bath under a nitrogen atmosphere and keeping it warm for 35 minutes, then adding ammonium persulfate and reacting for 3 hours to obtain a vinyl chloride copolymer emulsion; the amount ratio of di(2-ethylhexyl) succinate sulfonate, ammonia water, nonylphenol polyoxyethylene ether, water, silica sol, tert-butyl acrylate, hexafluorobutyl acrylate, vinyl chloride, dodecanol and ammonium persulfate is 2.5g:5mL:0.8g:10mL:40mL:8g:5.5g:13g:0.5g:0.7g; (4) adding soybean-based adhesive and MDI adhesive to the vinyl chloride copolymer emulsion, mixing evenly, to obtain a finishing film material; the amount ratio of soybean-based adhesive, MDI adhesive and vinyl chloride copolymer emulsion is 2g:2.5g:40g.

[0037] Furthermore, the lightweight green fireproof decorative panel also includes an edge banding strip, and the material of the edge banding strip is PVC.

[0038] A preparation method of a lightweight green fireproof decorative panel comprises the following steps: S1, uniformly coating a decorative film material on the surface of an ultra-thin fiberboard, and hot pressing for 2 minutes at 140°C and 1.2MPa to form a decorative film with a thickness of 0.30mm; S2, then laminating the decorative film to the surface of a substrate, and then using a hot press to perform hot pressing and curing, the hot pressing conditions being: 160°C, 1.8MPa, and 15 minutes, to obtain a lightweight green fireproof decorative panel; S3, grinding the edge of the lightweight green fireproof decorative panel to make it smooth, and then using an edge banding strip to perform edge banding on the edge of the lightweight green fireproof decorative panel to obtain a finished lightweight green fireproof decorative panel.

[0039] Example 2

[0040] (1) A light green fireproof decorative panel, comprising a substrate, both sides of the substrate are laminated with ultra-thin fiberboard, and the outer side of the ultra-thin fiberboard is laminated with a decorative film material;

[0041] The substrate is prepared by the following steps:

[0042] The reed straw was steamed at 160°C for 9 minutes, and then placed in a hot mill at 190°C for 15 minutes to obtain reed straw hot fiber; 15 g of caffeic acid and 2 mL of 1.1 g / mL ascorbic acid solution were added to 80 g of reed straw hot fiber, and then 15 mL of 0.6 g / mL hydrogen peroxide solution was added, stirred at 80°C for 20 minutes, and then filtered and dried at 75°C for 22 hours to obtain reed straw fiber;

[0043] (2) Weigh shell powder and diatomaceous earth in a mass ratio of 1.8:1, and dry at 100°C until the water content is less than 0.4% to obtain a mixed filler; add the dried mixed filler into anhydrous ethanol and ultrasonically disperse it for 40 minutes, then add aluminum-titanium composite coupling agent JTW-1816 and react at 95°C for 18 minutes, filter and obtain a modified filler. The amount of aluminum-titanium composite coupling agent JTW-1816 added is 2.5% of the mass of the modified filler;

[0044] (3) Reed straw fiber, polypropylene resin, polyvinyl chloride resin, modified filler, MDI adhesive and soybean-based adhesive were mixed evenly in a mass ratio of 60:25:45:40:8:5, and extruded to obtain a substrate with a thickness of 2.5 mm.

[0045] The ultra-thin fiberboard has a thickness of 0.3 mm and a density of 1.0 g / m 3 .

[0046] The preparation method of the decorative film material is as follows: (1) sodium di(2-ethylhexyl) succinate sulfonate, water, and silica sol with a concentration of 25wt%, add dodecanol, ultrasonically disperse, adjust the system pH to 5.0, then add methacryloxymethyltrimethoxysilane, ultrasonicate for 25 minutes, and then stir at 250°C to obtain a silica sol solution, wherein the amount ratio of sodium di(2-ethylhexyl) succinate sulfonate, water, silica sol, dodecanol, and methacryloxymethyltrimethoxysilane is 4g:25mL:12mL:0.6g:6mL; (2) sodium di(2-ethylhexyl) succinate sulfonate, ammonia water, nonylphenol polyoxyethylene ether and water are mixed to obtain a mixed solution, adjust the silica sol solution to neutral and add the mixed solution, then add tert-butyl acrylate and propylene glycol; (3) heating the pre-emulsion to 78°C in a water bath under a nitrogen atmosphere and keeping the temperature for 30 min, then adding ammonium persulfate and reacting for 4 h to obtain a vinyl chloride copolymer emulsion; the amount ratio of di(2-ethylhexyl) succinate sulfonate, ammonia water, nonylphenol polyoxyethylene ether, water, silica sol, tert-butyl acrylate, hexafluorobutyl acrylate, vinyl chloride, dodecanol and ammonium persulfate is 4g:8mL:1g:15mL:45mL:8g:6.5g:15g:0.7g:1g; (4) adding soybean-based adhesive and MDI adhesive to the vinyl chloride copolymer emulsion, mixing evenly, to obtain a finishing film; the amount ratio of soybean-based adhesive, MDI adhesive and vinyl chloride copolymer emulsion is 2.5g:3.2g:50g.

[0047] Furthermore, the lightweight green fireproof decorative panel also includes an edge banding strip, and the material of the edge banding strip is PUR.

[0048] A preparation method of a lightweight green fireproof decorative panel comprises the following steps: S1, uniformly coating a decorative film material on the surface of an ultra-thin fiberboard, and hot pressing for 12 minutes at 145°C and 1.4MPa to form a decorative film with a thickness of 0.40mm; S2, then laminating the decorative film to the surface of a substrate, and then using a hot press to perform hot pressing and curing, and the hot pressing conditions are: 170°C, 1.6MPa, and time for 20 minutes to obtain a lightweight green fireproof decorative panel; S3, grinding the edge of the lightweight green fireproof decorative panel to make it smooth, and then using an edge banding strip to seal the edge of the lightweight green fireproof decorative panel to obtain a finished lightweight green fireproof decorative panel.

[0049] Example 3

[0050] A light green fireproof decorative panel comprises a substrate, both sides of the substrate are laminated with ultra-thin fiberboards, and the outer side of the ultra-thin fiberboard is laminated with a decorative film material;

[0051] The substrate is prepared by the following steps:

[0052] (1) The reed straw was steamed at 170°C for 8 min, and then placed in a hot mill at 200°C for 10 min to obtain reed straw hot fiber; 18 g of caffeic acid and 3 mL of 1 g / mL ascorbic acid solution were added to 100 g of reed straw hot fiber, and then 20 mL of 0.5 g / mL hydrogen peroxide solution was added, and the mixture was stirred at 90°C for 10 min, and then filtered and dried at 80°C for 20 h to obtain reed straw fiber;

[0053] (2) Weigh shell powder and diatomaceous earth in a mass ratio of 2:1, and dry at 100°C until the water content is less than 0.5% to obtain a mixed filler; add the dried mixed filler into anhydrous ethanol and ultrasonically disperse it for 50 minutes, then add aluminum-titanium composite coupling agent JTW-1816 and react at 100°C for 15 minutes, and filter to obtain a modified filler. The amount of aluminum-titanium composite coupling agent JTW-1816 added is 2.8% of the mass of the modified filler;

[0054] (3) Reed straw fiber, polypropylene resin, polyvinyl chloride resin, modified filler, MDI adhesive and soybean-based adhesive were mixed evenly in a mass ratio of 70:30:55:50:10:8, and extruded to obtain a substrate with a thickness of 3 mm.

[0055] The ultra-thin fiberboard has a thickness of 0.45 mm and a density of 1.1 g / m 3 .

[0056] The preparation method of the decorative film material is as follows: (1) sodium di(2-ethylhexyl) succinate sulfonate, water, and silica sol with a concentration of 30wt%, add dodecanol, ultrasonically disperse, adjust the system pH to 5.5, then add methacryloxymethyltrimethoxysilane, ultrasonicate for 30 minutes, and then stir at 260°C to obtain a silica sol solution, wherein the amount ratio of sodium di(2-ethylhexyl) succinate sulfonate, water, silica sol, dodecanol, and methacryloxymethyltrimethoxysilane is 5.5g:30mL:15mL:0.8g:8mL; (2) sodium di(2-ethylhexyl) succinate sulfonate, ammonia water, nonylphenol polyoxyethylene ether and water are mixed to obtain a mixed solution, adjust the silica sol solution to neutral and add the mixed solution, then add tert-butyl acrylate and acrylic acid Hexafluorobutyl ester, vinyl chloride and dodecanol to obtain a pre-emulsion; (3) heating the pre-emulsion to 80°C in a water bath under a nitrogen atmosphere and keeping it warm for 25 minutes, then adding ammonium persulfate and reacting for 5 hours to obtain a vinyl chloride copolymer emulsion; the amount ratio of di(2-ethylhexyl) succinate sulfonate, ammonia water, nonylphenol polyoxyethylene ether, water, silica sol, tert-butyl acrylate, hexafluorobutyl acrylate, vinyl chloride, dodecanol and ammonium persulfate is 5.5g:10mL:1.2g:20mL:50mL:10g:7.5g:18g:0.8g:1.2g; (4) adding soybean-based adhesive and MDI adhesive to the vinyl chloride copolymer emulsion, mixing evenly, to obtain a decorative film material; the amount ratio of soybean-based adhesive, MDI adhesive and vinyl chloride copolymer emulsion is 3g:4g:60g.

[0057] Furthermore, the lightweight green fireproof decorative panel also includes an edge banding strip, and the material of the edge banding strip is EVA.

[0058] A preparation method of a lightweight green fireproof decorative panel comprises the following steps: S1, uniformly coating a decorative film material on the surface of an ultra-thin fiberboard, and hot pressing at 150°C and 1.2MPa for 12 minutes to form a decorative film with a thickness of 0.50mm; S2, then laminating the decorative film to the surface of a substrate, and then using a hot press to perform hot pressing and curing, the hot pressing conditions being: 180°C, 1.8MPa, and 20 minutes to obtain a lightweight green fireproof decorative panel; S3, grinding the edge of the lightweight green fireproof decorative panel to make it smooth, and then using an edge banding strip to perform edge banding on the edge of the lightweight green fireproof decorative panel to obtain a finished lightweight green fireproof decorative panel.

[0059] The soy-based adhesive was purchased from Ningbo Zhongke Zhaolu New Materials Co., Ltd.; the ultra-thin fiberboard was purchased from Jining Wood Industry Sanlian Co., Ltd.

[0060] Comparative Example 1

[0061] The same as Example 2, except that an equal mass of acrylic acid is used instead of caffeic acid to prepare reed straw fiber.

[0062] Comparative Example 2

[0063] The same as Example 2, except that the same mass of titanate coupling agent JTW-101 is used instead of aluminum-titanium composite coupling agent JTW-1816.

[0064] Comparative Example 3

[0065] The same as Example 2, except that the reed straw fiber, polypropylene resin, polyvinyl chloride resin, modified filler, MDI adhesive and soybean-based adhesive are uniformly mixed in a mass ratio of 60:25:45:40:5:1.

[0066] Comparative Example 4

[0067] The same as Example 2, except that the preparation method of the decorative film material is as follows: (1) sodium di(2-ethylhexyl) succinate sulfonate, water, and silica sol with a concentration of 25wt%, add dodecanol, ultrasonically disperse, adjust the system pH to 5.0, then add methacryloxymethyltrimethoxysilane, ultrasonically disperse for 25 minutes, and then stir at 250°C to obtain a silica sol solution, wherein the amount ratio of sodium di(2-ethylhexyl) succinate sulfonate, water, silica sol, dodecanol, and methacryloxymethyltrimethoxysilane is 4g:25mL:12mL:0.6g:6mL; (2) sodium di(2-ethylhexyl) succinate sulfonate, ammonia water, nonylphenol polyoxyethylene ether and water are mixed to obtain a mixed solution, and then tert-butyl acrylate, hexafluorobutyl acrylate, vinyl chloride and dodecanol are added. , to obtain a pre-emulsion; (3) heating the pre-emulsion to 78°C in a water bath under a nitrogen atmosphere and keeping it warm for 30 minutes, then adding ammonium persulfate and reacting for 4 hours to obtain a vinyl chloride copolymer emulsion; the amount ratio of di(2-ethylhexyl) succinate sulfonate, ammonia water, nonylphenol polyoxyethylene ether, water, silica sol, tert-butyl acrylate, hexafluorobutyl acrylate, vinyl chloride, dodecanol, and ammonium persulfate is 4g:8mL:1g:15mL:8g:6.5g:15g:0.7g:1g; (4) adjusting the silica sol to neutral, then adding the silica sol, soybean-based adhesive, and MDI adhesive to the vinyl chloride copolymer emulsion, mixing evenly, to obtain a decorative film material; the amount ratio of the silica sol, soybean-based adhesive, MDI adhesive, and vinyl chloride copolymer emulsion is 28g:2.5g:3.2g:22g.

[0068] Performance testing: According to the GB / T17657-2022 testing method, the finished lightweight green fire-retardant decorative panels prepared in Example 1-Example 3 and Comparative Example 1-Comparative Example 4 were tested; among them, the flame retardant performance test was carried out in accordance with GB / T8624-2012, and the results are shown in Table 1.

[0069] Table 1. Performance test

[0070] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Water absorption (%) 2.8 2.5 2.3 9.9 6.4 14.7 5.3 Dip stripping length (mm) 3.8 4.4 3.3 15.5 12.3 10.8 11.2 Surface bonding strength (MPa) 1.47 1.52 1.50 1.50 1.32 1.28 1.14 Internal bonding strength (MPa) 0.98 0.91 0.83 0.45 0.56 0.38 0.89 Surface resistance to cold and hot cycles No cracks, bubbles or wrinkles No cracks, bubbles or wrinkles No cracks, bubbles or wrinkles No cracks, bubbles or wrinkles There are cracks, bubbles and wrinkles No cracks, bubbles or wrinkles There are cracks <![CDATA[Formaldehyde emission (mg / m 3 ).]]> 0.005 0.004 0.003 0.004 0.005 0.005 0.004 Surface hardness (H) 3 3 3 3 3 3 3 Wear resistance (mg / 100r) 22.3 25.1 24.6 25.5 25.8 26.2 32.9 Flame retardant grade A2 A2 A2 A2 A2 A2 A2 Surface pollution resistance level Level 5 Level 5 Level 5 Level 5 Level 5 Level 5 Level 5

[0071] As can be seen from Table 1, the light green fireproof decorative panels prepared by Examples 1 to 3 of the present application are waterproof and moisture-proof, have high wear resistance, high bonding strength, good impregnation and peeling performance, are cold-resistant and heat-resistant, pollution-resistant, have excellent flame retardant properties, and have almost zero formaldehyde emission, and are safe and environmentally friendly. Combining Comparative Examples 1 to 4, it can be seen that the ratio of caffeic acid-modified reed straw fiber, filler modified by bimetallic aluminum-titanium composite coupling agent JTW-1816, and adhesive has a great influence on internal bonding strength and impregnation and peeling performance, and the preparation of vinyl chloride copolymer emulsion has a great influence on surface bonding strength and surface wear resistance, while cold and heat resistance is related to the preparation of vinyl chloride copolymer emulsion and the modification of reed straw fiber.

[0072] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.

Claims

1. A light green fireproof decorative panel, characterized in that: The invention comprises a substrate, both sides of which are bonded with ultra-thin fiberboards, and the outer side of the ultra-thin fiberboards is bonded with a decorative film material; the substrate comprises reed straw fiber, polypropylene resin, polyvinyl chloride resin, modified filler, MDI adhesive, and bean-based adhesive; the mass ratio of the reed straw fiber, polypropylene resin, polyvinyl chloride resin, modified filler, MDI adhesive, and bean-based adhesive is (50-70): (20-30): (35-55): (30-50): (5-10): ( 3-8); the facing film material comprises vinyl chloride copolymer emulsion, silica sol and methacryloxymethyl trimethoxysilane; the substrate is prepared by the following steps: (1) steaming reed straw at 150-170°C for 8-10 min, and then hot grinding at 180-200°C in a hot grinder for 10-20 min to obtain reed straw hot fiber; adding caffeic acid and 1-1.2 g / mL ascorbic acid solution to the reed straw hot fiber, and then adding 0.5-0.8 g / mL L of hydrogen peroxide solution, stirring at 70-90°C for 10-30 minutes, then filtering and drying to obtain reed straw fiber, wherein the amount ratio of the reed straw hot fiber, caffeic acid, ascorbic acid and hydrogen peroxide solution is (50-100) g: (10-18) g: (2-3) mL: (10-20) mL; (2) weighing shell powder and diatomaceous earth according to a mass ratio of (1.5-2): 1, drying at 100°C until the water content is less than 0.3-0.5%, and obtaining a mixed Filler; add the dried mixed filler into anhydrous ethanol and ultrasonically disperse for 30-50 minutes, then add aluminum-titanium composite coupling agent JTW-1816 and react at 90-100°C for 15-20 minutes, filter and obtain a modified filler, wherein the amount of aluminum-titanium composite coupling agent JTW-1816 added is 2-2.8% of the mass of the mixed filler; (3) mix reed straw fiber, polypropylene resin, polyvinyl chloride resin, modified filler, soybean-based adhesive and MDI adhesive, extrude and mold to obtain a base material.

2. A light green fireproof decorative panel according to claim 1, characterized in that: The ultra-thin fiberboard has a thickness of 0.25-0.45 mm and a density of 0.9-1.1 g / m 3 .

3. A light green fireproof decorative panel according to claim 2, characterized in that: The thickness of the substrate described in claim 2 is 2-3 mm.

4. A light green fireproof decorative panel according to claim 3, characterized in that: The preparation method of the decorative film material is as follows: (1) mixing sodium di(2-ethylhexyl) succinate sulfonate, water, and silica sol with a concentration of 20-30wt%, adding dodecanol, ultrasonically dispersing, adjusting the pH of the system to 4.5-5.5, then adding methacryloxymethyltrimethoxysilane, ultrasonically dispersing for 20-30 minutes, and then stirring at 240-260°C to obtain a silica sol solution, wherein the sodium di(2-ethylhexyl) succinate sulfonate, water, silica sol, dodecanol, The dosage ratio of methacryloyloxymethyltrimethoxysilane is (2.5-5.5) g: (20-30) mL: (10-15) mL: (0.5-0.8) g: (5-8) mL; (2) di(2-ethylhexyl) sodium sulfosuccinate, ammonia water, nonylphenol polyoxyethylene ether and water are mixed to obtain a mixed solution, the silica sol solution is adjusted to neutral and added to the mixed solution, and then tert-butyl acrylate, hexafluorobutyl acrylate, vinyl chloride and dodecanol are added to obtain a pre-emulsified solution. ; (3) heating the pre-emulsion to 75-80°C in a water bath under a nitrogen atmosphere and keeping the temperature for 25-35 minutes, then adding ammonium persulfate and reacting for 3-5 hours to obtain a vinyl chloride copolymer emulsion; the amount ratio of the sodium di(2-ethylhexyl) succinate sulfonate, ammonia water, nonylphenol polyoxyethylene ether, water, silica sol liquid, tert-butyl acrylate, hexafluorobutyl acrylate, vinyl chloride, dodecanol, and ammonium persulfate is (2.5-5.5) g: (5-10) mL: (0.8-1.2 )g:(10-20)mL:(40-50)mL:(8-10)g:(5.5-7.5)g:(13-18)g:(0.5-0.8)g:(0.7-1.2)g; (4) Add soybean-based adhesive and MDI adhesive into vinyl chloride copolymer emulsion, mix evenly, and obtain a decorative film material; the dosage ratio of soybean-based adhesive, MDI adhesive and vinyl chloride copolymer emulsion is (2-3)g:(2.5-4)g:(40-60)g.

5. A light green fireproof decorative panel according to claim 4, characterized in that: Including edge banding strips, the material of the edge banding strips is any one of EVA, ABS, PVC, and PUR.

6. A method for preparing a lightweight green fireproof decorative panel according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, evenly apply the facing film material on the surface of the ultra-thin fiberboard, and hot press for 10-12 minutes at 140-150℃ and 1.2-1.6MPa to form a facing film with a thickness of 0.30-0.50mm; S2, then adhere the facing film to the surface of the substrate, and then use a hot press to heat press and cure it. The hot pressing conditions are: 160-180℃, 1.5-1.8MPa, and time 15-20min to obtain a lightweight green fireproof decorative panel.

7. The method for preparing a light green fireproof decorative panel according to claim 6, characterized in that: Also includes: S3, grind the edges of the lightweight green fireproof veneer panels to make them smooth, and then use edge banding strips to seal the edges of the lightweight green fireproof veneer panels.

Citation Information

Patent Citations

  • Light fiber composite plate and production method thereof

    CN109049259A

  • Environment-friendly high-density fiberboard and preparation method thereof

    CN117841136A

  • Environment-friendly PVC (polyvinyl chloride) veneer and preparation method thereof

    CN118478612A

Cited By

  • Fireproof, moistureproof, wear-resistant and corrosion-resistant inorganic sheet and preparation method thereof

    CN121779079A